2017
DOI: 10.3390/s17040885
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Single-Nucleotides by Tunneling Current Measurements at Sub-MHz Temporal Resolution

Abstract: Label-free detection of single-nucleotides was performed by fast tunneling current measurements in a polar solvent at 1 MHz sampling rate using SiO2-protected Au nanoprobes. Short current spikes were observed, suggestive of trapping/detrapping of individual nucleotides between the nanoelectrodes. The fall and rise features of the electrical signatures indicated signal retardation by capacitance effects with a time constant of about 10 microseconds. The high temporal resolution revealed current fluctuations, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Signal retardation by RC effects can be a possible explanation for the anomalous feature as the larger external resistance is expected to give smaller pulses, which in turn suggests that the resistance component contributing to the temporal response of ionic current was actually not the resistance at the pore but the access resistance outside the channel. 9,10,23,24 To investigate the intriguing observations in more detail, the RC time constant τ was extracted from the resistive pulses measured (Figure 2d). More than 100 pulses were first merged into one pulse by arithmetic averaging, and the tail portion of the averaged signal (defined as the region where the ionic current falls in a window between 15 and 1% from the pulse top) was fitted exponentially by I ion = I 0 exp(−t/τ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signal retardation by RC effects can be a possible explanation for the anomalous feature as the larger external resistance is expected to give smaller pulses, which in turn suggests that the resistance component contributing to the temporal response of ionic current was actually not the resistance at the pore but the access resistance outside the channel. 9,10,23,24 To investigate the intriguing observations in more detail, the RC time constant τ was extracted from the resistive pulses measured (Figure 2d). More than 100 pulses were first merged into one pulse by arithmetic averaging, and the tail portion of the averaged signal (defined as the region where the ionic current falls in a window between 15 and 1% from the pulse top) was fitted exponentially by I ion = I 0 exp(−t/τ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Meanwhile, in this method, it is a prerequisite to be very sure what actually observed in the ionic current measurements is of transient ion blockage associated with the translocation of single particles since the charging/discharging at the stray capacitance may cause a considerable influence on the current signals. , More specifically, it has recently been reported that this effect may significantly retard the temporal response of ionic current against the ion blockade phenomena occurring upon the fast translocation of single particles through a nanopore. An equivalent circuit model , has been proposed to describe the signal retardation, , wherein the degree of signal smearing is expressed by a time constant given as the product of stray capacitance and resistance.…”
mentioning
confidence: 99%
“…Technical improvements in the experimental set-ups and fabrication processes would facilitate this task. Taniguchi and colleagues, for example, recently showed that extra coatings on the nanoelectrodes could bring improvements in terms of the signal-tonoise ratio and bandwidth of the measurements 53,54 .…”
Section: Protein Sequencing Using Tunnelling Currentsmentioning
confidence: 99%
“…70 This would not only improve the resolution of DNA sequence but could also speed up the process of base calling. 71 Theoretically, this could be further improved by solid-state nanopores engineered from synthetic materials, such as graphene or carbon nanotubes. Indeed, in a 2010 study by Garaj et al, a graphene nanopore showed electrical variations as a single molecule of DNA was translocated through the pore.…”
Section: Nanopore Advancesmentioning
confidence: 99%